Grounding God: Religious Responses to the Anthropocene - Conty, Arianne ca. 21. Jh. (State University of New York Press, 2023)
Now that we have entered a new geological age called The Anthropocene, which indicates that humanity has infiltrated the natural world in such irreversible ways that nature and culture can no longer be separated, the Modern dichotomies of mind versus body and culture versus nature have become implausible, and will need to be replaced. This book will claim that it is in the field of religion that we can find a new ontology better suited for the Anthropocene Age. I call this new religious ontology the grounding of the sacred, in that it seeks to deconstruct the binaries of modernity and provide in their place a revalorization of the immanent earth and the more-than-human beings that inhabit it. Such a grounding of the sacred is a potent means to overcome the exploitation and desecration of the earth and its non-human beings, and to provide in its place an inclusive cosmopolitics that extends mind into matter, and culture into nature. Tracing such a grounding in the Christian, Buddhist, Neo-Pagan and Animist traditions, this book will seek to elaborate an interdisciplinary ecosophy using philosophy, anthropology and religious studies in order to provide new values for the Anthropocene Age